ON THE RELATIONS BETWEEN BODY, KNOWLEDGE AND NATURE IN THOMAS AQUINAS (Fiep Bulletin - online, 2014)
The objective of this study refers to investigate the epistemic functions of body as regards to the knowledge of natural objects, according to the theory of knowledge developed by the philosopher Tomas Aquinas. For this purpose, they will be revisited the relations between sensitivity, intellectuality, body movement, virtue and playfulness into one of the main works of this thinker, the book Suma Teológica. After proper explanation of these concepts, the final considerations of the study will emphasize the links between game and recreation for the philosopher, as well as their influences along the cognition that seeks to understand the nature.
Keywords: Body; Knowledge; Nature; Cognition; Tomas Aquinas